2020
DOI: 10.4103/njms.njms_161_20
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the role of local host factors in the candidal colonization of oral cavity: A review update

Abstract: Human oral cavity is home to a number of organisms, Candida albicans being one of them. This review article aims at understanding the correlation between the oral candidal colonization and the local host factors that may influence it with special emphasis on congenital craniofacial anomalies such as cleft lip and palate (CLP). Various scientific databases were searched online and relevant articles were selected based on the inclusion criteria. A comparative study was done to understand t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…All the included articles were published between 1992 and 2022. These studies included two retrospective studies 25 -see Table 1, two review studies 26,27 -see Table 2, and the remaining (n = 28) were observational studies as shown in Table 3. Of these 28 observational studies, seven were prospective studies, [28][29][30][31][32][33][34] five were cohort studies, 2,23,35,36 ten were case-control studies, 11,16,17,[37][38][39][40][41][42][43] and finally, six were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…All the included articles were published between 1992 and 2022. These studies included two retrospective studies 25 -see Table 1, two review studies 26,27 -see Table 2, and the remaining (n = 28) were observational studies as shown in Table 3. Of these 28 observational studies, seven were prospective studies, [28][29][30][31][32][33][34] five were cohort studies, 2,23,35,36 ten were case-control studies, 11,16,17,[37][38][39][40][41][42][43] and finally, six were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
“…Patients with xerostomia had a higher risk of developing oral candidiasis and oral fungal growth than non-xerostomia groups [13] . In addition, another study on the presence of local host factors, including xerostomia, orofacial clefts, dentures, fixed orthodontic appliances (FOA) and oral mucous membrane atrophy, found that these lead to a significant increase in Candida colonization [14] . C. albicans is the most common fungal infection, usually occurring in very young and older patients.…”
Section: Epidemiologymentioning
confidence: 99%
“…Studies show that the colonization rate of oral Candida species is high in CLP patients. [ 7 8 ] Children with CLP require several hospital visits and multiple surgeries at different stages of life till adulthood. Poor health status and use of orthodontic appliances and oral prosthetics increase the susceptibility of CLP patients to Candida -related infections as a result of poor health status.…”
Section: Introductionmentioning
confidence: 99%
“…Poor health status and use of orthodontic appliances and oral prosthetics increase the susceptibility of CLP patients to Candida -related infections as a result of poor health status. [ 7 9 ] C. albicans is the most isolated species, but other non-albicans Candida species including C. glabrata, C. tropicalis, C. parapsilosis , and C. krusei also contribute significantly. [ 10 11 ] Recurrent infections and development of resistance toward conventional antifungal drugs such as diflucan or fluconazole (FLC) make treatment of such secondary infections challenging.…”
Section: Introductionmentioning
confidence: 99%